Dopant site in indium-doped SrTiO3 photocatalysts. Issue 34 (19th August 2020) - Sudrajat, Hanggara; Fadlallah, Mohamed M.; Tao, Shuxia; Kitta, Mitsunori; Ichikuni, Nobuyuki; Onishi, Hiroshi
Abstract : Occupation site of In guest dopant in SrTiO3 host lattice is successfully revealed and comprehensively studied with combined experimental and theoretical methods. Abstract : Strontium titanate, SrTiO3, with the perovskite ABO3 structure is known as one of the most efficient photocatalyst materials for the overall water splitting reaction. Doping with appropriate metal cations at the A site or at the B site substantially increases the quantum yield to split water into H2 and O2 . The site occupied by the guest dopant in the SrTiO3 host thus plays a key role in dictating the water splitting activity. However, little is known about the detailed structure of the dopant site in the host lattice. In this study, the local structure of In 3+ cations, which were shown to improve the water splitting activity of SrTiO3, is investigated with X-ray absorption fine structure spectroscopy and density functional theory (DFT) calculations. The In 3+ cations exclusively substitute for Ti 4+ cations at the B site to form InO6 octahedra. Further optical experiments using UV-Vis diffuse reflectance spectroscopy and DFT calculations of the density of states indicate that the substitution of In 3+ for Ti 4+ does not alter the band structure and bandgap energy (remaining at 3.2 eV). The mechanism underlying the increased water splitting activity is discussed in relation to occupation of the B site by In 3+ cations.